Effort Comparisons for a Class of Four-Player Tournaments - Deren Caglayan; Emin Karagözoglu; Kerim Keskin; Cagri Saglam (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We propose a novel tournament design that incorporates the main properties of a round-robin tournament, a Swiss tournament, and a race. Following an equilibrium analysis, we compare 36 tournament structures inherent in our model and several well-known tournament models from the literature, on the basis of expected total equilibrium effort. We show that two of the tournament structures we introduce outperform all the other tournament structures considered.
Keywords: C72; 330; contest; multi-player contest; race; round-robin tournament; Swiss tournament; tournament